Analysis of oxidation products of α-tocopherol in extra virgin olive oil using liquid chromatography–tandem mass spectrometry. (15th February 2020) - Tanno, Rena; Kato, Shunji; Shimizu, Naoki; Ito, Junya; Sato, Shuntaro; Ogura, Yusuke; Sakaino, Masayoshi; Sano, Takashi; Eitsuka, Takahiro; Kuwahara, Shigefumi; Miyazawa, Teruo; Nakagawa, Kiyotaka
Highlights: References of α-tocopherol hydroperoxide (Toc-OOH) stereoisomers were prepared. LC–MS/MS method for Toc-OOH stereoisomers and α-tocopherylquinone (TQ) was developed. Toc-OOH and TQ in fresh/oxidized extra virgin olive oil (EVOO) were analyzed. Photo-irradiation to EVOO increased Toc-OOH stereoisomers but not TQ. In contrast, thermal oxidation of EVOO increased TQ but not Toc-OOH stereoisomers. Abstract: When α-tocopherol (α-Toc) exerts its antioxidative effect, a portion of α-Toc is converted to certain oxidation products. Although accumulation of such oxidation products is considered to cause a deterioration in the quality of foods, their distribution and generation in food samples have been still unknown. In this study, we tried to analyze α-Toc hydroperoxide (Toc-OOH) stereoisomers and tocopherylquinone (TQ) in extra virgin olive oil (EVOO) using liquid chromatography-tandem mass spectrometry. Photo-irradiation (5000 lx) to EVOO increased Toc-OOH stereoisomers but not TQ. In contrast, thermal oxidation (150 °C) of EVOO increased TQ but not Toc-OOH. We considered that the generation of Toc-OOH and TQ were due to the [4+2]-cycloaddition reaction and proton donation from the phenolic hydrogen, respectively. Our data and method would be helpful for understanding of α-Toc oxidation mechanisms in edible oil samples or the estimation of food quality.